2009
DOI: 10.2166/wh.2009.071
|View full text |Cite
|
Sign up to set email alerts
|

Turbidity and chlorine demand reduction using locally available physical water clarification mechanisms before household chlorination in developing countries

Abstract: Over 1.1 billion people in the world lack access to improved drinking water. Diarrhoeal and other waterborne diseases cause an estimated 1.9 million deaths per year. The Safe Water System (SWS) is a proven household water treatment intervention that reduces diarrhoeal disease incidence among users in developing countries. Turbid waters pose a particular challenge to implementation of SWS programmes; although research shows that a 3.75 mg l 21 sodium hypochlorite dose effectively treats turbid waters, users som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 17 publications
0
18
0
3
Order By: Relevance
“…However, other investigations have documented greater efficacy of settling and decanting alone as a pretreatment mechanism that significantly reduces turbidity and chlorine demand (Kotlarz et al 2009). The difference between the two studies is that water was settled for 24 hours in the settling and decanting efficacy study, while settling occurred for only 2 hours in this study.…”
Section: Discussionmentioning
confidence: 64%
“…However, other investigations have documented greater efficacy of settling and decanting alone as a pretreatment mechanism that significantly reduces turbidity and chlorine demand (Kotlarz et al 2009). The difference between the two studies is that water was settled for 24 hours in the settling and decanting efficacy study, while settling occurred for only 2 hours in this study.…”
Section: Discussionmentioning
confidence: 64%
“…Previous laboratory research investigating the turbidity and chlorine demand reduction of cloth filtration, sand filtration, and settling and decanting in 10-300 NTU waters found all three locally available physical filtration mechanisms were effective in reducing turbidity. 32 However, cloth filtration did not reduce turbidity at 10 NTU, but reduced turbidity more effectively as initial turbidity increased to 300 NTU. The cloth filtration turbidity reduction results are consistent with results presented herein, with no turbidity reduction seen in lowturbidity (< 20 NTU) sources.…”
Section: Discussionmentioning
confidence: 94%
“…Further research on locally available mechanisms to reduce chlorine demand and turbidity is not indicated in the laboratory setting because this research has already been well established in the literature. 32,33 Targeted research in specific locations where household chlorination is promoted with known high concentrations of THM precursors, such as bromine, is indicated. Bromine presence increases the health risks associated with THMs, as brominated THMs, with higher risk and therefore lower guideline values than chloroform, are formed.…”
Section: Discussionmentioning
confidence: 99%
“…To represent various turbidity types seen in surface water used for drinking in low-resource settings, reactors were spiked with laboratory-grade white kaolin clay (Lion China Clay USP, Charles B. Chrystal Co., Larchmont, NY, US) or creek bottom sediments collected from the Mystic River (Medford, MA, US). The 0, 10, 30, 100, and 300 NTU targets were set to be consistent with previous research and with chlorine dose breakpoints [16,32,33]. Pre-testing was conducted to determine the amount of clay/sediments required to obtain turbidity targets in reactors using a calibrated Hach 2100 portable turbidimeter (Loveland, CO, US).…”
Section: Turbiditymentioning
confidence: 99%